Reaction of pineapple germplasm inoculated with Fusarium moniliforme var. subglutinans - Cabral, José Renato S.; Matos, Aristóteles P. de; Souto, Gernack F. (Pesquisa Agropecuaria Brasileira, 2014)
The pineapple rot, caused by Fusarium moniliforme var. subglutinant (FMS), is the limiting factor for the expansion of this crop in Brazil. To detect new sources of resistance to the pathogen, the cultivars BGA-6, BGA-16, Fernando Costa, Inerme CM, Inerme de Rondônia, Manteiga, Perolera, Red Spanish and Rondon, all of them from the Brazilian Pineapple Germplasm Collection, were inoculated by immersion of the wounded base of the slips in a suspension of 105 conidia of FMS per ml, for three minutes. The cultivar Pérola was used as susceptible control. Evaluation 100 days after inoculation showed that 'Perolera', 'BGA-6', 'Inerme CM' and 'Fernando Costa' were resistant to FMS. Observations of longitudinal stem sections of resistant plants showed the presence of small necrosis around the site of inoculation. Attempts to isolate the pathogen from the necrotic areas did not result in fungal growth. Cultivars varied on their susceptibility to FMS.
Keywords: ananas comosus; fusariosis; gummosis; evaluation for resistance